Marketing Management Innovations: Unraveling the Interplay of Brand Positioning, Market Segmentation, and Consumer Engagement - Tirta Mulyadi; PA Andiena Nindya Putri; Rosento Rosento; Yenni Kurnia Gusti; Sabil Sabil (Dinasti Publisher, 2024)
In the dynamic landscape of modern marketing, innovative strategies are essential for businesses to thrive. This article delves into the intricate interplay between brand positioning, market segmentation, and consumer engagement within the realm of marketing management. Brand positioning forms the cornerstone of effective marketing, defining how a brand is perceived in the minds of consumers relative to competitors. Market segmentation further refines this process by dividing heterogeneous markets into distinct groups with similar needs and preferences. By understanding these segments, marketers can tailor their strategies to resonate with specific consumer demographics. However, in the digital age, consumer engagement has emerged as a critical factor driving marketing success. Engaging consumers goes beyond traditional advertising; it involves creating meaningful interactions and fostering relationships through various channels, including social media, content marketing, and experiential events. The synergy among brand positioning, market segmentation, and consumer engagement is paramount for achieving sustainable competitive advantage and fostering brand loyalty in today's hypercompetitive markets. This article explores how innovative approaches in marketing management leverage the intricate connections between brand positioning, market segmentation, and consumer engagement to drive business growth and cultivate enduring relationships with consumers.